El concepto de soberanía en la teoría constitucional colombiana del siglo XIX - Uribe Álvarez, Roberth (2023)
This paper analyzes some of the ways in which the concept of sovereignty was understood by Colombian constitutional theorists of the nineteenth century. The relevance of this analysis arises from the importance that the term sovereignty has had during the formation of the constitutional republican theory in Colombia. On the basis of this concept, several of the central problems of the theory of (c onstitutional) rule of law were and are being discussed. Colombian constitutional theorists of the nineteenth century studied this theory. The conceptual and discursive analysis proposed here understands constitutionalism, from an internal point of view, a s a metalanguage on written constitutional law.